Electrochemical performance of silicon thin film anodes covered by diamond-like carbon with various surface coating morphologies - Kim, Sang-Ok; SHIM, HEUNG TAEK; Lee, Joong Kee (Springer Verlag, 2010)
Four different kinds of diamond-like carbon (DLC) coating morphologies on the surface of silicon films were prepared directly on a copper foil by using radio frequency plasma-enhanced chemical vapor deposition at 200 A degrees C. A thin double layer film consisting of DLC (60 nm) and silicon film (250 nm) was fabricated for use as the anode material of lithium secondary batteries, and its electrochemical performance was also examined with special attention being paid to the surface coverage of the DLC film. The full coverage of silicon by the DLC film resulted in poor capacity due to the ensuing low reactivity with the lithium ions. On the other hand, the partial coating of the DLC film on the silicon film not only reduced the capacity fading, but also increased the discharge capacity during the charge/discharge cycles. These results indicated that the good dispersion of the DLC coating, obtained by using a smaller coating sector on the silicon film, improved the integrity of the electrode structure, thus giving higher capacities and reduced capacity fading.